LÖCHER IM NETZ. ZWISCHEN DEN ZEILEN DER LEIBNIZ-KORRESPONDENZ - MICHAEL KEMPE (Lexicon Philosophicum)
This article investigates the ‘gaps’ in the learned correspondences of the early modern respublica literaria in Europe by the example of the huge correspondence of the philosopher and universal scholar Gottfried Wilhelm Leibniz (1646-1716). It shows that intentionally non-written letters, being a lack of answer or an explicite silence, have to be interpreted as a part of the epistolary relation between the members of the republic of letters. Although these unwritten and unspoken messages are hard to be detected and can not be published in any edition they belong to a correspondence network as well as a written letter or a given answer